2016
DOI: 10.1002/anie.201600035
|View full text |Cite
|
Sign up to set email alerts
|

End‐Group‐Functionalized Poly(α‐olefinates) as Non‐Polar Building Blocks: Self‐Assembly of Sugar–Polyolefin Hybrid Conjugates

Abstract: Living coordinative chain-transfer polymerization of α-olefins, followed by chemical functionalization of a Zn(polymeryl)2 intermediate, provides entry to end-group functionalized poly(α-olefinates) (x-PAOs) that can serve as a new class of non-polar building block with tailorable occupied volumes. Application of these x-PAOs for the synthesis and self-assembly of sugar-polyolefin hybrid conjugates demonstrate the ability to manipulate the morphology of the ultra-thin film nanostructure through variation in oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
66
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 63 publications
0
66
0
Order By: Relevance
“…The further growth of polymer chains initiating from (polyolefinyl) 2 Zn may be useful for the syntheses of PO-based block copolymers [27]. Syntheses of polyethylene-block-polyester and polyethylene-block-polyether have been attempted with POs functionalized with -OH end groups, which were generated by treatment of the CCTP product (polyolefinyl) 2 Zn with O 2 [28][29][30][31]. We also discovered a method to grow polystyrene (PS) chains initiating from (polyolefinyl) 2 Zn that allows the syntheses of commercially more relevant PO-block-PS and PS-block-PO-block-PS in one-pot [32][33][34][35].…”
Section: Methodsmentioning
confidence: 99%
“…The further growth of polymer chains initiating from (polyolefinyl) 2 Zn may be useful for the syntheses of PO-based block copolymers [27]. Syntheses of polyethylene-block-polyester and polyethylene-block-polyether have been attempted with POs functionalized with -OH end groups, which were generated by treatment of the CCTP product (polyolefinyl) 2 Zn with O 2 [28][29][30][31]. We also discovered a method to grow polystyrene (PS) chains initiating from (polyolefinyl) 2 Zn that allows the syntheses of commercially more relevant PO-block-PS and PS-block-PO-block-PS in one-pot [32][33][34][35].…”
Section: Methodsmentioning
confidence: 99%
“…We have previously reported that sugar-polyolefin conjugates can be conveniently obtained through the chemical linking of apolar saccharide "head" group with ahydrophobic "tail" derived from an end-group functionalized poly(aolefinate) (xPAO)o ft unable molecular weight and very narrow molecular weight distribution, also known as polydispersity. [16,17] Thex PAOp recursors are,i nt urn, prepared through the transition-metal-mediated living coordinative chain transfer polymerization (LCCTP) of acommon a-olefin monomer,s uch as propene and 4-methyl-1-pentene (4M1P). [18] Importantly,t hrough programmed variations in molecular weight and the space-filling requirements of the polyolefin pendant side chain, awide variety of occupied free volumes for the hydrophobic domain of sugar-polyolefin conjugates can be easily designed and synthesized.…”
mentioning
confidence: 99%
“…[18] Importantly,t hrough programmed variations in molecular weight and the space-filling requirements of the polyolefin pendant side chain, awide variety of occupied free volumes for the hydrophobic domain of sugar-polyolefin conjugates can be easily designed and synthesized. [16] In the present report, ultra-low molecular weight amorphous, atactic azido-terminated poly(4-methyl-1-pentene) (N 3 -aPMP) (2), with an umber-average molecular weight index, M n ,o f1 .0 kDa and ap olydispersity index, (= M w / M n ), of 1.05, where M w is the weight-average molecular weight index, was prepared through the LCCTP of af ixed amount of 4M1P using previously published methods. [16,18] As shown in Figure 2, sugar-polyolefin conjugate 1 was next prepared in high yield through the copper-mediated "click" reaction between 2 and the cellobiose propargyl amide derivative 3.A fter purification, matrix-assisted laser desorption ionization (MALDI) mass spectrometry of 1 provided M n and values of 1.4 Da and 1.05, respectively,a nd this material was shown to exist by 1 HNMR spectroscopy as an on-interconverting 3:1m ixture of b and a stereochemical anomers.…”
mentioning
confidence: 99%
“…[1][2][3][4] Potentially,t he macromolecular engineering of PE through the control of its primary structure (that is,c haracteristics such as average molar mass,m olarmass distribution (MMD), [5][6][7][8] branching density,a nd the introduction of functional groups [9][10][11][12][13] )isexpected to fabricate new polyolefin-based high value-added materials.T he development of new catalysts for coordination polymerizations led to significant advances for high-density PE synthesis,enabling living polymerizations,end-group functionalities,and copolymerization with polar monomers.I nc ontrast, similar advances for low-density PE remain aformidable challenge,despite the continuous developments in the field of controlled radical polymerizations (CRPs,o rr eversible-deactivation radical polymerizations,RDRPs).…”
mentioning
confidence: 99%